2011
DOI: 10.1590/s0034-737x2011000200001
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de embriões zigóticos e desenvolvimento in vitro de coquinho-azedo

Abstract: Germination of zygotic embryos and in vitro development of Butia capitata (Mart.) Becc.The objective of this work was to evaluate the effects of light, Murashige & Skoog (MS) salts concentration and sucrose on the in vitro embryo germination and plantlet development of Butia capitata (Mart.) Becc. The culture medium consisted of MS salts supplemented with vitamins, myo-inositol, hydrolyzed casein, activated charcoal, sucrose and agar. Zygotic embryos were cultured in the light and in the dark. Different concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
2
10
0
9
Order By: Relevance
“…After around 14 days, the embryo elongated, and after 28 days, around 80% of embryos germinated. In Butia capitata, 38.8% of the embryos presented the first leaf sheath after 28 days of in vitro culture in MS medium without growth regulators, including gibberellins, suggesting that its use could optimize embryo germination (RIBEIRO et al, 2011). Gibberellins are plant hormones that promote growth and stimulate cell elongation and division.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After around 14 days, the embryo elongated, and after 28 days, around 80% of embryos germinated. In Butia capitata, 38.8% of the embryos presented the first leaf sheath after 28 days of in vitro culture in MS medium without growth regulators, including gibberellins, suggesting that its use could optimize embryo germination (RIBEIRO et al, 2011). Gibberellins are plant hormones that promote growth and stimulate cell elongation and division.…”
Section: Resultsmentioning
confidence: 99%
“…Disinfestation procedures typically include the use of distilled water, sodium hypochlorite, calcium hypochlorite, mercuric chloride, and other substances (GAMBORG;PHILLIPS, 1995). In Butia capitata, the disinfestation of zygotic embryos was successful by immersion in a 0.25% solution of chlorine for 10 min (RIBEIRO et al, 2011). Gibberellins (GAs) like gibberellic acid (GA 3 ) promote seed germination in many species of plants by stimulating the growth of the embryo and inducing the production of hydrolases that weaken the structures around the embryo (LOPES et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Em razão disso, não se recomenda seu armazenamento por longos períodos, principalmente quando os frutos já atingiram a maturidade fisiológica ou quando as sementes apresentaram teores de umidade inferiores a 40%. (RIBEIRO et al, 2011). Embriões zigóticos imaturos de Astrocaryum ulei apresentaram maior porcentagem de germinação em meio contendo 30 g L -1 de sacarose, comparativamente aos embriões maduros.…”
Section: Discussionunclassified
“…Nunes et al (2008) assessed different concentrations of sucrose and physiological stages of fruit ripening in germination of Jatropha and found that a higher concentration of sucrose (60 gL -1 ) provided a higher number of germinated immature embryos (83.68%). Ribeiro et al (2011) obtained no roots or leaf sheaths in plantlets from embryos of mature fruits grown in medium without sucrose, and associated with result of lack of carbohydrate reserves sufficient for full plant development.…”
Section: Germination Of Embryosmentioning
confidence: 99%